Analysis of reflection from a novel anisotropic lossy medium characterized by particular material properties. Issue 8 (24th May 2017) - Khalid, Muhammad; Tedeschi, Nicola; Frezza, Fabrizio
Abstract: In this paper, we investigate the reflection characteristics of a novel electric–magnetic uniaxial lossy medium, characterized by extreme material properties and having optic axis in a generic direction. The novelty of the medium is specified by particular material parameters: very large transverse and very small axial components of permittivity and permeability with respect to the optic axis of the medium. To study the reflection, we consider an interface between a simple isotropic medium and the uniaxial medium defined by the complex permittivity and permeability tensors. Electromagnetic response of the medium is analyzed under different situations by considering various orientations of the plane of incidence and by arbitrarily choosing the direction of the optic axis. We emphasize the importance of direction of the optic axis and discuss its influence on electromagnetic reflection from the interface. It is noted that this novel material exhibits a very interesting property of behaving like a perfect absorber or a perfect reflector depending upon the orientation of the optic axis. Moreover, we also observe a Brewster's angle like effect where the interface shows total transmission for the co-component of the incident wave while total reflection for the cross-component. An analytical relation for this Brewster-like angle is also presented. This property may enable the material to find applications in the realization of polarization inverters.